2015
DOI: 10.1086/683797
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Kepler Phase Curves and Secondary Eclipses: Temperatures and Albedos of Confirmed Kepler Giant Planets

Abstract: We present a comprehensive study of phase curves and secondary eclipses in the Kepler data set using all data from 16 quarters that were available in 2013-2014. Our sample consists of 20 confirmed planets with R p > 4R e , P < 10d, V mag < 15. Here we derive their temperatures and albedos, with an eye towards constraining models for the formation and evolution of such planets. Where there was overlap our results confirm parameters derived by previous studies, whereas we present new results for Kepler 1b-8b, 12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
139
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(162 citation statements)
references
References 88 publications
21
139
2
Order By: Relevance
“…The depth of the planetary eclipse would imply a planet-tostar surface brightness ratio of f = (8.93 ± 4.13) × 10 −4 , allowing us to constrain the geometric A g and Bond A b albedo of the planet. From the effective stellar temperature, eccentricity, and scaled semi-major listed in Table 5, and assuming A g = 1.5 × A B and heat redistribution factor between 1/4 and 2/3, we found tentative values of A g = 0.055 ± 0.028, A B = 0.037 ± 0.019, and a planet brightness temperature of T br = 1950±250 K. This would make Kepler-423b one of the gas-giant planets with lowest Bond albedo known so far (see, e.g., Angerhausen et al 2014). …”
Section: Secondary Eclipse and Planet Albedosupporting
confidence: 55%
“…The depth of the planetary eclipse would imply a planet-tostar surface brightness ratio of f = (8.93 ± 4.13) × 10 −4 , allowing us to constrain the geometric A g and Bond A b albedo of the planet. From the effective stellar temperature, eccentricity, and scaled semi-major listed in Table 5, and assuming A g = 1.5 × A B and heat redistribution factor between 1/4 and 2/3, we found tentative values of A g = 0.055 ± 0.028, A B = 0.037 ± 0.019, and a planet brightness temperature of T br = 1950±250 K. This would make Kepler-423b one of the gas-giant planets with lowest Bond albedo known so far (see, e.g., Angerhausen et al 2014). …”
Section: Secondary Eclipse and Planet Albedosupporting
confidence: 55%
“…However, as we noted and Angerhausen et al (2014) concluded as well, the detection of the secondary eclipse is neither clear nor conclusive. Moreover, given their derived mass for this companion with a Jupiter-like radius, it is difficult to explain their proposed stellar nature.…”
Section: Resultsmentioning
confidence: 56%
“…Based on transit-fitting analysis and a claimed detection of the secondary eclipse, Esteves et al (2013) concluded that the object emits light so they rejected it as a planet. In contrast, Angerhausen et al (2014) provided a high-level analysis of the entire light-curve (encompassing all available Kepler observations). They detected several dimmings in the phase-folded light-curve, achieved similar conclusions as Lillo-Box et al (2014b), and suggested that the detected dimmings are poorly explained with a secondary eclipse alone.…”
Section: Introductionmentioning
confidence: 99%
“…The inferred geometric albedo, A g = 0.25-0.38 (4,6,7,10,14), reveals a planet of reflectivity comparable to the solar system giants (A g = 0.4-0.5), which is unexpectedly high for a close-in gas planet. Theory indeed predicts that the strong stellar irradiation that a planet in such an orbit experiences strips off reflective clouds, rendering the planet dark (A g < 0.1) (22,25).…”
mentioning
confidence: 88%